Chest wall reconstruction with biological mesh, rib stabilization, and latissimus dorsi rotation: A case report - Lucía Fein; Bruno Cuturi; Ruver Berazategui; Sylvia Duarte (Elsevier, 2024)
Introduction: Children with chest wall tumors may require extensive chest wall resections. The reconstruction of large chest wall defects can be surgically challenging. We present a new chest wall reconstruction method. Case presentation: A 2.5-year-old male who developed respiratory symptoms and chest pain was diagnosed with an Askin's tumor of the left chest wall. The tumor originated in the posterior segments of the seventh and eighth ribs. Computed tomography of the chest revealed a large mass filling the left hemithorax, causing flattening of the hemidiaphragm and mediastinal shift. No distant metastases were identified. The patient underwent six cycles of neoadjuvant chemotherapy with vincristine, adriamycin, cyclophosphamide, ifosfamide, and etoposide. Post-chemotherapy, magnetic resonance imaging revealed a significant reduction in tumor size. The patient was taken to the operating room for the resection of the tumor. The posterior segments of the left sixth, seventh, eighth, and ninth ribs were surgically excised. The chest wall was reconstructed using a biological mesh (Permacol™), sutures for costal arch stabilization using the lattice technique, and a rotated latissimus dorsi muscle flap for defect coverage. An 18 Fr pleural drainage was left in place. The patient tolerated the operation well and was successfully extubated 48 hours later. Pain was effectively managed via paravertebral block. The patient was discharged on the 14th postoperative day. The resected specimen had negative margins. He subsequently underwent several more cycles of chemotherapy. Eighteen months after the operation he has developed no scoliosis and has full range of motion on the left chest wall. Conclusion: A combination of a biological mesh, rib stabilization and latissimus dorsi rotation seems to be a valid technique to cover large chest wall defects.